2019
DOI: 10.1039/c9cs00203k
|View full text |Cite|
|
Sign up to set email alerts
|

The evolution of spiropyran: fundamentals and progress of an extraordinarily versatile photochrome

Abstract: Spiropyrans have played a pivotal role in the emergence of the field of chromism following their discovery in the early 20th century, with almost ubiquitous use in materials applications especially since their photochromism was discovered in 1952.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
416
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 503 publications
(463 citation statements)
references
References 162 publications
6
416
0
2
Order By: Relevance
“…As a third method to determine guest:host ratios, we used solution 1 H NMR experiments, i. e. the host is decomposed by an acid (DCl) and in the resulting DMSO‐ d 6 solution the proton signals of the MOF linker (here: terephthalic acid) and the guest (here: SP−O) are integrated to obtain the desired ratios . During our experiments we found that DCl does not only decompose the MOF framework, but also SP−O is protonated and starts to decompose . In “fast” (5 min after addition of DCl) NMR experiments on compounds 1 , 2 and 3 (Figure S16, S17 and S18, Supporting Information) we observed SP−O:MOF ratios of 0.99 : 1 ( 1 ), 0.15 : 1 ( 2 ) and 0.20 : 1 ( 3 ), which are, for 2 and 3 , in reasonable agreement with those obtained from XPS measurements (Table ) showing that the latter is an elegant, non‐destructive way to analyse such systems quantitatively.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…As a third method to determine guest:host ratios, we used solution 1 H NMR experiments, i. e. the host is decomposed by an acid (DCl) and in the resulting DMSO‐ d 6 solution the proton signals of the MOF linker (here: terephthalic acid) and the guest (here: SP−O) are integrated to obtain the desired ratios . During our experiments we found that DCl does not only decompose the MOF framework, but also SP−O is protonated and starts to decompose . In “fast” (5 min after addition of DCl) NMR experiments on compounds 1 , 2 and 3 (Figure S16, S17 and S18, Supporting Information) we observed SP−O:MOF ratios of 0.99 : 1 ( 1 ), 0.15 : 1 ( 2 ) and 0.20 : 1 ( 3 ), which are, for 2 and 3 , in reasonable agreement with those obtained from XPS measurements (Table ) showing that the latter is an elegant, non‐destructive way to analyse such systems quantitatively.…”
Section: Resultsmentioning
confidence: 98%
“…[9] During our experiments we found that DCl does not only decompose the MOF framework, but also SPÀ O is protonated and starts to decompose. [56][57][58] In "fast" (5 min after addition of DCl) NMR experiments on compounds 1, 2 and 3 (Figure S16, S17 and S18, Supporting Information) we observed SPÀ O:MOF ratios of 0.99 : 1 (1), 0.15 : 1 (2) and 0.20 : 1 (3), which are, for 2 and 3, in reasonable agreement with those obtained from XPS measurements ( Table 2) showing that the latter is an elegant, non-destructive way to analyse such systems quantitatively.…”
Section: Composition (Degree Of Loading)mentioning
confidence: 99%
“…These changes express themselves in terms of color change or visible deformation on the macro-scale. In recent years, many scientists have prepared a large number of artificial muscles with a specific mechanical strength and light-driven ability by adding organic phases to the polymeric systems, e.g., azobenzene [ 91 ] or spiropyran [ 92 ], or inorganic phases, e.g., graphene [ 93 ], or metal nanoparticles [ 94 , 95 ]. In comparison to thermal-responsive polymers, light-induced polymers have the unique advantages of instantaneous control, environmental friendliness, non-contact initiation, etc., which is of importance in the aerospace, biomedical, and other fields.…”
Section: Applications Of Shape-memory Polymeric Artificial Musclesmentioning
confidence: 99%
“…Systems with fast bleaching are required for photochromic lenses or real-time holography [12][13], while for many biological applications, adaptation of the bleaching rate to meet specific process is key [10,[14][15]. An extensive literature explores structure-properties relationships in hexaarylbiimidazole [16], spiropyrane and spirooxazine [17] or azobenzene [18][19][20] derivatives as well as less common molecules [21][22]. With some of these Tphotochromes, the impact of metal coordination on photoswitching has been explored and recognized as a valuable strategy to effectively adapt the system properties as well as to design sensors [23].…”
Section: Introductionmentioning
confidence: 99%